Symptomatic Radial-Sided Tears of the Triangular Fibrocartilage Complex: An All-Arthroscopic Repair Using Bone Anchors - Choudhury, Muntasir M.; Yap, Robert T. J.; Chia, Dawn S. Y.; Sajeev, Suraj; Alizada, Ghulam S.; Jiang, Jackson K. H. (Journal of Wrist Surgery, 2022)
Radial-sided tears of the triangular fibrocartilage, though uncommon, can still be a reason for ulnar-sided wrist pain, and, at times, instability of the distal radioulnar joint. Historically, it has been believed that because of the paucity of vascularity along the radial edge of the triangular fibrocartilage complex (TFCC), any form of repair will not lead to healing, thus stating it to be an exercise in futility. Current literature deftly argues against this previously prevailing concept and supports the need of repair in case of symptomatic radial-sided TFCC tears. In our study, we describe an all-arthroscopic technique of repairing radial-sided tears using a bone anchor which can be a fast and simple procedure in the hands of an orthopaedic or hand surgeon trained in arthroscopy. This technique also circumvents the risk of injuring the superficial radial nerve and other radial-sided structures which are stated complications of the current arthroscopic repairs.
Keywords: arthroscopy; triangular fibrocartilage complex; DRUJ; radial-sided TFCC tears; ulnar-sided wrist pain